LIFE IMPRISONMENT: SHORTCOMINGS OF PUNISHMENT EXECUTION - Малярчук, Назар Вікторович; Мороз, Марина Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Objective: is an attempt to investigate, detect and address the existing shortcomings in the legal regulation of the execution of sentences in the form of life imprisonment, as well as the conditions for serving prisoners in Ukraine. Analyze foreign experience with respect to the execution of sentences in the form of life imprisonment. Methods: analytical, dialectical, comparative-legal, formal-logical. Results: were proposed the ways to improve national legislation in the context of the execution of sentences in the form of life imprisonment. Discussion: about the process of execution of punishment in the form of life imprisonment and serving this type of punishment by convicts in Ukraine, given the opinion of domestic scientists on this occasion. Life imprisonment for Ukrainian legislation and sciences, is a dignified new and specific type of punishment. Its introduction was conditioned by the international requirements of the Council of Europe to democratic countries in which places such punishment, as opposed to death penalty. The moratorium on the use of the death penalty, as the worst case in the history of mankind, is one of the crucial steps of Ukraine’s rapprochement with the international community as an independent European state. Today there is a limited number of nautical works devoted to life imprisonment. Unfortunately, most of all, the distorted type of appeal is considered in terms of deprivation of liberty for a certain period of time and in the framework of criminal-law investigations, albeit, for some reason, without taking into account the provisions of the legal regulation of criminal-executive legislation. In these circumstances, the research of such punishment as life imprisonment is very important. It’s execution form and conditions, type of punishment by convicts in the light of the provisions of the criminal-executive legislation is quite relevant too.